2006
DOI: 10.1039/b510018f
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular architectures assembled by the interaction of purine nucleobases with metal-oxalato frameworks. Non-covalent stabilization of the 7H-adenine tautomer in the solid-state

Abstract: The synthesis, crystal structure and variable-temperature magnetic measurements of the compounds [Mn(mu-ox)(H2O)(7H-pur-kappaN9)]n (1), {[Mn(mu-ox)(H2O)2].(7H-ade).(H2O)}n (2) and {[Cu(mu-ox)(H2O)(7H-ade-kappaN9)][Cu(mu-ox)(mu-H2O)(7H-ade-kappaN9)]. approximately 10/3H2O}n (3), (where ox: oxalato dianion, pur: purine, and ade: adenine) are reported. Compounds 1and 2 contain one-dimensional chains in which manganese(II) atoms are bridged by bis-bidentate oxalato ligands. The distorted octahedral geometry around… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 85 publications
3
51
0
Order By: Relevance
“…The existence of other Ade tautomers was evidenced by experimental studies (García-Terán et al, 2006;Gu & Leszczynski, 1999;Lührs et al, 2001;Stepanyugin et al, 2002a;Sukhanov et al, 2003), often in the presence of a metal (Samijlenko et al, 2004;Vrkic et al, 2004). It was also found that the Ade imino tautomer is more stabilized under the influence of charged platinum (Burda et al, 2000) or mercury (Zamora et al, 1997) cations.…”
Section: Elementary Molecular Mechanisms Of the Spontaneous Point Mutmentioning
confidence: 99%
“…The existence of other Ade tautomers was evidenced by experimental studies (García-Terán et al, 2006;Gu & Leszczynski, 1999;Lührs et al, 2001;Stepanyugin et al, 2002a;Sukhanov et al, 2003), often in the presence of a metal (Samijlenko et al, 2004;Vrkic et al, 2004). It was also found that the Ade imino tautomer is more stabilized under the influence of charged platinum (Burda et al, 2000) or mercury (Zamora et al, 1997) cations.…”
Section: Elementary Molecular Mechanisms Of the Spontaneous Point Mutmentioning
confidence: 99%
“…[23][24][25][26] In recent years the influence of hydrogen bonding interactions and molecular recognition on tautomeric and protonation equilibria has received growing interest and a few examples have been reported in the literature, where a noncanonical nucleobase tautomer is stabilized by a properly positioned H bond acceptor. [27][28][29] Salt and co-crystal formation are popular approaches to optimize the physicochemical properties of a pharmaceutically relevant solid without modifying the molecule itself. [30][31][32] It is well-established that the solid-state properties of a pharmaceutical solid have a significant impact on drug performance.…”
Section: Introductionmentioning
confidence: 99%
“…3 The interest of these systems stems from the desire to better understand the complex interactions often present in a great diversity of molecular biorecognition processes 4 and to offer a powerful tool for the efficient synthesis of advanced functional materials with tailor-made properties and potential applications for the therapeutic medicine 5 and the material sciences. 6 Most of the studies concerning DNA/RNA nucleobases have been realized in gas phase or aqueous media, 7 but notable advances have been made in the solid-state chemistry such as (without being exhaustive): (a) the design and improvement of chemical biology tools and/or pharmaceutical agents, 8 (b) the building of high-dimensional covalent architectures containing nucleobases as bridging or terminal ligands, 9 (c) the stabilization of noncanonical tautomers through interactions with metallic ions 10 and/or hydrogen-bonding donor/acceptor species, 1,11 and (d) the development of artificial receptors for specific DNA/RNA bases recognition for their use as nucleotide sensors or for the determination of low concentrations of therapeutic agents. 12 Following these lines of investigation, we have recently reported the elaboration and solid-state characterization of supramolecular architectures isolated from aqueous solution at physiological pH in which adenine aggregates reside between neutral one-dimensional (1D) metal-oxalato-water complexes to build sheetlike structures containing sequentially arranged organic and inorganic layers.…”
Section: Introductionmentioning
confidence: 99%